M&A of listed companies: What, when and how to communicate to the market? - Meneses Battifora, María Angélica (2025)
M&A transactions of listed companies may have additional complexities compared to those of private companies, as they are subject to securities market regulations. This article will explore the information that must be reported to the Securities Market Superintendency and to the market in general, as well as the guidelines that must be observed to comply with the applicable regulations.